CRIMINAL LIABILITY OF A JUVENILE PERSON ON BREAKING OF TRAFFIC REGULATIONS - Zauere, Karina (Administrative and Criminal Justice, 2019)
In implementing of the norms provided for by the section 260, article 2 of the of the Republic of Latvia Criminal Law into practice (for breaking of traffic provisions or provisions regarding vehicle operation, if it has been committed by a person operating a vehicle and as a result thereof serious bodily injury has been caused to the victim or death of a person has been caused thereby, the applicable punishment is deprivation of liberty for a period up to eight years, with deprivation of the driver’s licence for a period up to five years), the legislator has not taken into account that this violation may be committed by a minor. It results from the analysis of the provisions of Section 260, article 2, section 7, article 3, and section 65, article 2 stems that section 260, article 2 is a less serious crime, for which a minor is not punishable with deprivation of liberty – the sole main punishment intended by the sanction of the provision in question. Therefore, the appropriate punishment for the committing of such a crime resulting in a death of a person and/or serious bodily injury that threatens the life of a person cannot be applied to a juvenile person. With respect to the specifics of criminal liability of juvenile persons for the violation of section 260, article 2 as it is laid down by the Criminal Law the basic punishment – imprisonment for a period exceeding eight years – is not applicable to juvenile persons. Only the additional punishment of deprivation of the driver’s licence for a period of up to five years, which is disproportionate to the harm caused. In order to enable the application of the basic punishment for the committing of the crime as set out by section 260, article 2 of the Criminal Law ( legal effects: death of a person and/or serious bodily injury), it is necessary to amend the sanction of section 260, , article 2 to the imprisonment for a period exceeding eight years. Subsequently, such an amendment would re-classify the crime as a severe crime committed through negligence and for the committing which the basic punishment – imprisonment would be applicable, as it was most likely intended by the legislator.